Employer perceptions of migrant candidates' suitability: the influence of decision‐maker and organisational characteristics. (5th November 2015) - Fernando, Mario; Almeida, Shamika; Dharmage, Shyamali C
Abstract : This paper reports on how decision‐makers' personal characteristics and organisational characteristics can influence the screening of immigrant professionals during the recruitment and selection process. The sample consisted of 220 decision‐makers in the engineering industry working in New South Wales, Australia. The results show White/Anglo Australian decision‐makers had more suitability concerns of ethnic migrant candidates during the recruitment and selection process than decision‐makers of other ethnicities. However, this was moderated by organisational characteristics of size and clientele. Decision‐makers in larger organisations and a diverse ethnic client base showed less suitability concerns of migrant candidates during the recruitment and selection process. Key points: Organisational decision‐makers are faced with rapidly changing workforce demographics during the recruitment and selection process. Decision‐makers' personal characteristics and organisational characteristics can influence suitability of ethnic minority migrant candidates. When suitability concerns decrease, decision‐makers are more willing to employ ethnic migrant candidates. Decision‐makers' extent of training and development on cultural diversity and equal employment opportunities are important factors in determining migrant employment outcomes.